Sleep pattern, aggressive behavior and substance use among school students of Manipur: A cross-sectional study - Markordor Lyngdoh; Brogen Singh Akoijam; R K S. Agui; Kh Sonarjit Singh (Wolters Kluwer Medknow Publications, 2019)
Background: Adolescence is a vulnerable period of growth and development. This is the time when habits are inculcated which will carry forward to adult life. Sleeping patterns among adolescents have an impact on their overall health. Early substance use initiation is a serious concern because it is associated with significantly increased risks for developing substance use disorders. In general, aggressive behaviors progress from less to more severe over the course of adolescent development. Objectives: The objectives of this study are to determine the lifestyle behaviors of young adolescents focusing on sleep pattern, aggressive behavior, and substance use. Methods: A cross-sectional study was conducted among 739 students of Class VII and VIII in both government and private schools in Imphal West and Kangpokpi districts of Manipur between August 27 and September 25, 2017. A pretested, structured questionnaire was used, which included the modified version of Buss and Perry Aggression Questionnaire. The data were analyzed using the IBM SPSS software (IBM SPSS for Windows, Version 21.0. Armonk, NY, USA). Results: Only 56.2% of the students had adequate sleep. The proportion of adolescents using alcohol, tobacco, cigarettes, and Ganja was 4.6%, 9.5%, 5.7%, and 1.6%, respectively. Aggressive behavior was shown by 35.3%. Male students were getting more sleep (60.7%), were more aggressive (38.8%), and were using tobacco and cigarettes (82.4%) more than female students. Conclusions: Around two-fifth of the adolescents were not getting enough sleep. The association between aggressive behavior and substance use was found but needs further investigation for its temporal relationship.